IMPLEMENTASI PELAYANAN PERIZINAN BERBASIS ELEKTRONIK MELALUI SISTEM ONLINE SINGLE SUBMISSION RISKED BASED APPROACH (OSS RBA) DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU (PMPTSP) KABUPATEN MALUKU TENGAH - WALLA, NONA; NORMAWATI, NORMAWATI (Patria Artha University, 2024)
This research aims to determine the implementation of electronic-based licensingservices through OSS RBA at the Central Maluku Regency PMPTSP Service, and todetermine the factors that hinder and facilitate the implementation of electronic-basedlicensing services through RBA OSS at the Central Maluku Regency PMPTSP Service.The type of research in this research is qualitative research, research informants consistof department heads, licensing services section, RBA OSS operational team and thecommunity. Data collection techniques are carried out through observation, interviewsand documentation. The data analysis technique uses qualitative analysis in the form ofdata reduction, data presentation, data verification and drawing conclusions. Theresearch results found that the implementation of electronic-based licensing services hasbeen implemented through OSS RBA at the PMPTSP Service of Central Maluku Regency.In the licensing of service businesses implemented online, it refers to policy regulations,institutional existence and digitalization. It can be seen that regulations as regulatorypolicies have been implemented in the implementation of services, in accordance with theinstitutions of the PMPTSP Service as well as digitalized service delivery to make iteasier for the public to process permits. There are inhibiting factors that influence theimplementation of electronic-based licensing through OSS RBA at the Central MalukuRegency PMPTSP Service. Overlapping regulatory systems between central and regionalin this case refer to Law Number 23 of 2014 with Government Regulation Number 5 of2021 and document requirements and information and knowledge related to OSS RBA,lack of socialization regarding the OSS-RBA application by the public, lack ofunderstanding of Inconsistency in applicable regulations and OSS RBA maintenance, inthis case the WiFi network used, is an obstacle in improving the quality of publicservices.